Portfolio adjustment and panic behavior under true uncertainty - Se Ho Kwak (University of Massachusetts, Department of Economics, 2022)
G.L.S. Shackle was one of the representative critics against probability-based economic theory, and influenced some Post-Keynesians and Austrians. During the 1980s and 1990s, his alternative framework was mathematically reconstructed by Katzner. In this paper, we will reformalize the Shackle-Katzner framework to explain the financial decision-making of the individual. For this, the portfolio diversification between two non-monetary assets will be explained by the reformalized model introduced here, and then moved to the analysis about a case of money and a non-monetary asset. Based on these findings, a few possible scenarios of panic behavior in the portfolio adjustment will be examined.
Keywords: 330